2017
DOI: 10.1145/3158103
|View full text |Cite
|
Sign up to set email alerts
|

Migrating gradual types

Abstract: Gradual typing allows programs to enjoy the benefits of both static typing and dynamic typing. While it is often desirable to migrate a program from more dynamically-typed to more statically-typed or vice versa, gradual typing itself does not provide a way to facilitate this migration. This places the burden on programmers who have to manually add or remove type annotations. Besides the general challenge of adding type annotations to dynamically typed code, there are subtle interactions between these annotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Comparison. Our tool uses the same input format as the tool that accompanies the paper by Campora et al [2018]. This enables a head-to-head comparison of our tool and their tool, for our benchmarks.…”
Section: Implementation and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison. Our tool uses the same input format as the tool that accompanies the paper by Campora et al [2018]. This enables a head-to-head comparison of our tool and their tool, for our benchmarks.…”
Section: Implementation and Experimental Resultsmentioning
confidence: 99%
“…Notice that for every benchmark, the type produced by their tool is ⊑-related to the type produced by our tool. For six benchmarks, the types are different, for three benchmarks the types are the same, and for one benchmark, no maximal migration exists but the tool from [Campora et al 2018] produces a type anyway. The differences highlight that the tool from [Campora et al 2018] may produce non-maximal migrations.…”
Section: Benchmarkmentioning
confidence: 99%
“…However, often the most static migration of a gradually typed program is not unique, and so the programmer wants to pick the most performant migration amongst the set of possibilities. The following program, adapted from [Campora et al 2018], illustrates the non-uniqueness of most-static migrations. In this example, a type annotation may be added to the parameter fixed or to widthFunc, but not to both.…”
Section: Program Migration Scenariosmentioning
confidence: 99%
“…if (fixed): widthFunc(fixed) else: widthFunc(5) Campora et al [2018] reported hundreds of different ways to maximize static typing in larger programs. Since each of the most-static migrations may have significantly different performance profiles, it is important that the programmer can make a rational selection among them.…”
Section: Program Migration Scenariosmentioning
confidence: 99%
See 1 more Smart Citation